2018
DOI: 10.3389/fgene.2018.00544
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cells: Emergent Nature of Tumor Emergency

Abstract: A functional analysis of 167 genes overexpressed in Krebs-2 tumor initiating cells was performed. In the first part of the study, the genes were analyzed for their belonging to one or more of the three groups, which represent the three major phenotypic manifestation of malignancy of cancer cells, namely (1) proliferative self-sufficiency, (2) invasive growth and metastasis, and (3) multiple drug resistance. 96 genes out of 167 were identified as possible contributors to at least one of these fundamental proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 445 publications
0
9
0
Order By: Relevance
“…Extensive work has shown that CSCs from primary prostate tumors or established cancer cell lines can be isolated from a heterogeneous population using cell surface markers, such as CD44 and CD133, aldehyde dehydrogenase (ALDH) activity using the ALDEFLUOR assay, and Hoechst dye to identify the side population [ 62 - 63 ] . Isolation of prostate CSCs has been performed by several groups.…”
Section: Prostate Cancer Stem-like Cellsmentioning
confidence: 99%
“…Extensive work has shown that CSCs from primary prostate tumors or established cancer cell lines can be isolated from a heterogeneous population using cell surface markers, such as CD44 and CD133, aldehyde dehydrogenase (ALDH) activity using the ALDEFLUOR assay, and Hoechst dye to identify the side population [ 62 - 63 ] . Isolation of prostate CSCs has been performed by several groups.…”
Section: Prostate Cancer Stem-like Cellsmentioning
confidence: 99%
“…The high intracellular oxidation status in viral infections consists of decreased antioxidant enzymes such as catalase, glutathione peroxidase, glutathione reductase, as well as high levels of hydroxyl radicals. Of note, tumor growth and development is always accompanied by oxidative stress, which develops due to various inflammatory and immune reactions [80].…”
Section: Oxidative Stress Causes Dna Damage That Activates the Immunementioning
confidence: 99%
“…Nevertheless, the most important feature of CSCs, which distinguishes them from normal stem cells fundamentally, is their metastasizing capability that allows these cells to form the stromal microenvironment suitable for further development of tumor regardless of the initial cellular environment. This attribute is primarily associated with an ability of CSCs to retain a pluripotency outside the specific niches while being resistant to stemness-suppressing influence of normal tissue stroma [43], and determined by changes in expression of genes responsible for epithelial-to-mesenchymal transition [44][45][46].…”
Section: Discussionmentioning
confidence: 99%